Top 10 Countdown: Clinical Trials in Cardiology - Nichols, Emma Hitt (MD Conference Express, 2014)
Throughout the past year, results from multiple clinical trials in the field of cardiology have been released. This article reviews data that were released from the top 10 clinical trials in cardiovascular health during the past year.